2021
DOI: 10.7717/peerj.11024
|View full text |Cite
|
Sign up to set email alerts
|

A psychrometric model to assess the biological decay of the SARS-CoV-2 virus in aerosols

Abstract: There is increasing evidence that the 2020 COVID-19 pandemic has been influenced by variations in air temperature and humidity. However, the impact that these environmental parameters have on survival of the SARS-CoV-2 virus has not been fully characterised. Therefore, an analytical study was undertaken using published data to develop a psychrometric model to assess the biological decay rate of the virus in aerosols. This revealed that it is possible to describe with reasonable accuracy (R2 = 0.718, p < 0.0… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
29
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(32 citation statements)
references
References 55 publications
3
29
0
Order By: Relevance
“…A study of environmental SARS-CoV-2 in the rooms of quarantining confirmed positive cases found 29/55 surfaces in the rooms of symptomatic cases were positive for SARS-CoV-2 by RT-qPCR; however, no viable virus was isolated in cell culture. [38] As such, the contribution of fomites to the transmission of SARS-CoV-2 is controversial, [39] and remains relatively unknown, [25] in part due to no minimum infectious dose of SARS-CoV-2 being established, [40] hampering studies of transmission dynamics from surfaces.…”
Section: Sars-cov-2 Transmission Via Fomitesmentioning
confidence: 99%
See 4 more Smart Citations
“…A study of environmental SARS-CoV-2 in the rooms of quarantining confirmed positive cases found 29/55 surfaces in the rooms of symptomatic cases were positive for SARS-CoV-2 by RT-qPCR; however, no viable virus was isolated in cell culture. [38] As such, the contribution of fomites to the transmission of SARS-CoV-2 is controversial, [39] and remains relatively unknown, [25] in part due to no minimum infectious dose of SARS-CoV-2 being established, [40] hampering studies of transmission dynamics from surfaces.…”
Section: Sars-cov-2 Transmission Via Fomitesmentioning
confidence: 99%
“…[127] Further considerations should also be made when the air is cooler and drier, given that it has been shown that the SARS-CoV-2 virus survives in aerosols for considerably longer, [27,28,128] and the viral half-life is >10 times longer during the winter and autumn months compared with the summer. [25] Breaks and social interactions Similar to many other occupational settings, individuals in sport may have coffee and lunch breaks throughout the day. These breaks can become high SARS-CoV-2 transmission risk situations, due to multiple people congregating in one location (e.g.…”
Section: Scenariomentioning
confidence: 99%
See 3 more Smart Citations